Smart Moving-Spiral-Clothesline for Urban Society - Sirawit Chaihang; Supachai Puengsungwan (ASEAN Journal of Science and Engineering, 2021)
This paper presented a smart moving-spiral-clothesline for urban life. The design of the clothes dryer is flat and used in the manner of spiral movement. 3D models have been designed to show the basic component of the proposed smart clothesline. To evaluate the proposed system, the simulation results have been set up to show the operation of the proposed system. The proposed system of the clothes drying rack (spiral moving type) can support the drying weight of 2.5 kg per one drying time, which can save 68.2% of the space compared to old clothes drying (fix type). This, consequently, can assist in terms of movable space. The proposed system can also analyze the situation when dust affecting the drying may damage clothes from the simulation of the operation of the device and the sensor. It is found that the proposed equipment can be used in the actual design. In addition, t is necessary to adjust the light value to suit the installation area to prevent equipment failure.